Reproductive Health of Women with Epilepsy in India: An Observational Study - Kumar, Aadithya Narayan Sunil; Aghoram, Rajeswari; Keepanasseril, Aneesh; Nair, Pradeep P. (International Journal of Epilepsy, 2022)
Objectives Women with epilepsy (WWE) have special reproductive health needs. We compare menstrual disorders, obstetric outcomes, and patterns of contraceptive use among WWE in the reproductive age group to those without epilepsy.Methods Sixty WWE between the ages of 18 and 45 years were randomly selected from a hospital database, and 60 controls in the same age group were recruited from among their families or close contacts. A questionnaire adapted from the National Family Health Survey 5 (NFHS-5) was administered to collect data on menstrual patterns, obstetric outcomes, fertility preferences, and contraceptive use. Descriptive statistics were used. Graphical and cross-tabulations were used for comparisons. All statistics were performed on STATA version 14.2 (StataCorp, Texas, United States).Results The demographic characteristics including mean age, education, and occupational status were comparable. Dysmenorrhea requiring use of pain killers was more common among WWE (odds ratio [OR]: 3.01; 95% confidence interval [CI]: 1.11–8.72); other menstrual disorders were equally frequent. Spontaneous fetal loss was seen in 25 (21.9%) of 114 pregnancies in WWE and 22 (17.9%) of 123 among control women. Demand for family planning was satisfied in 21 (65.6%) of 32 eligible WWE and 23 (62.2%) of 37 controls with the most common method being female sterilization. WWE knew fewer methods of contraception compared with controls (median: 2; interquartile range [IQR]: 1.2 vs. 4; IQR: 2.5; p < 0.0001).Conclusion WWE had more dysmenorrhea and less knowledge of contraceptive methods compared with controls. Abnormal uterine bleeding, contraceptive use, and spontaneous fetal loss were similar in both groups.
Keywords: women with epilepsy; menstrual disorder; contraception